FAMILY ROPALOMERIDAE - Ale-Rocha, Rosaly (Zootaxa, 2016)
Ropalomeridae is a small family with most species distributed in the Neotropical Region, from Mexico to Argentina, and only one Nearctic species. In Colombia, eight species distributed in four genera have been found. This catalogue, based on the study of specimens and available literature records, summarizes and updates the information on the Colombian fauna.